Comments on “Rich debt, poor debt: assessing household indebtedness and debt repayment capacity” - PHANG, Sock Yong (Institutional Knowledge at Singapore Management University, 2017)
This paper assesses the system-wide impacts of Malaysia’s rising household debt.Malaysia’s household debt-to-GDP ratio (HDGR) increased from 76% in 2009 to 89%in 2016. This increase has raised concerns regarding the implications for householdfinancial resilience and banking system stability. The paper uses a micro-level datasetthat integrates income and debt to calculate financial margin (FM) and the probabilityof default (PD) for individuals at the baseline, and when subject to various shocks.This allows the estimation of loss to lenders in the event of default, and from there,the banking system’s debt-at-risk. The findings show that default is more likely forhouseholds with a debt service ratio of greater than 60%. For higher-incomeindividuals, default is more likely at a debt service ratio of greater than 80%. Afterestimating potential losses for the banking sector, the authors conclude that it issufficiently well capitalised to withstand default losses arising from unexpectedmacroeconomic and housing price shocks.